Alur Tujuan Pembelajaran dan Asasmen - Ninda Akilla; Nurhasanah Nurhasanah; Rani Saputri; Mustafiyanti Mustafiyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article aims to find out what the flow of learning objectives and Principles. The flow of learning objectives is a series of learning obectives that are arranged systematically and logically in the learning phase so that students can achieve learning which is the limit of learning echievement. The flow of learning objectives becomes a guide for teachers and students to achieve Learning outcomes at the end of a phase. Teachers can develop a flow of learning objectives, each according to the context and needs of students in the class taught. The government provides several examples of learning flows that can be directly used or modified, and creates guidelines for preparing teaching tools.Asement can be defined as the activity of collecting, analyzing and interpreting data or information about study participants and their environment to obtain an overview of the individual’s condition or environment.